Neotectonics of Southeast Jamaica Derived From Marine Seismic Surveys and Gravity Cores. Issue 11 (22nd November 2019) - Wright, Vanshan; Hornbach, Matthew; Brown, Lyndon; McHugh, Cecilia; Mitchell, Simon
Abstract: Tectonics in Southeast Jamaica is poorly understood, but the region may contain currently unknown faults that could generate large‐magnitude earthquakes. This study constrains tectonics in Southeast Jamaica by collecting and analyzing seismic and shallow sediment core data in and around Kingston Harbor. Seismic results reveal a previously unrecognized strike‐slip fault system that accommodates strain via a complex mix of compression and extension. The faults appear to be a blind extension of one major fault (i.e., The Bull Bay Strike‐Slip Fault) within the Enriquillo‐Plantain Garden Fault Zone. This fault system may represent significant hazards to Kingston Jamaica because the fault is active, located less than 5 km from the city, and a complete rupture of the fault could generate a M w 5.8–6.9 earthquake. Our analyses highlight the need for continued paleoseismic studies, both onshore and offshore Jamaica. Key Points: Kingston Harbor preserves records of Pleistocene to present blind faults The Harbor faults are an extension of an onshore strike‐slip fault in Southeast Jamaica Fault reactivating may generate a M w 5.8–6.9 earthquake